Bemerkungen zu einigen wenig bekannten Tineidae in Europa (Lepidoptera) - Gaedike, Reinhard (Acta entomologica slovenica (Ljubljana), 2004)
There are hitherto 243 species of tineid moths known in Europe. Only 141 species are known from numerous localities, what allows to make some statements about the type of distribution for these taxa. The knowledge about the remaining 102 species is still very poor. 62 species are known only from their type locality, and another 40 species are known only from a few localities.
Keywords: Europe; Evropa; favna; Lepidoptera; molji